Sistem Kendali Lampu Defect Dan Reject Berbasis Web Server Menggunakan Raspberrry Pi 3 Model B - Endang Supriyadi; Maya Sofiana; Surya Dwipangga (Jurnal Teknik Informatika, 2021)
Abstract— This research covers the design and construction of a Web-based Defect & Reject Light Control Intelligent System with Raspberry Pi with the aim of detecting the quality conditions of manufactured goods at the final inspection section of PT. Suryaraya Rubberindo Industries. This system requires several components such as a Raspberry Pi 3 Microcontroller, Relays, mini filament LED lamps and several other supporting components. The design and construction of a Web-Based Defect & Reject Light Control Intelligent System with the Raspberry Pi comes from experimental results, besides that it is also supported by several literary documents found in journals and reference books. This Intelligent Web-Based Defect & Reject Light Control System with the Raspberry Pi uses a website design as an input to turn off or turn on a lamp. Two mini filament lamps are used as output components that are made like Signal lamps. Based on the results of the experiments conducted, the Web-Based Defect & Reject Light Control Intelligent System with the Raspberry Pi can work quite well. When this system detects the condition of the production goods in a state that does not meet the specified company standards but has a low level of seriousness (defect), the system will give a signal for a yellow light with a value of 1, whereas if the level of seriousness is high (reject) then the control system will give a signal to turn on the red light the value of the number 1 stored in the database